Chemical Analysis of Ethanolic Extract of Ripe Fruit, N-Hexane Fraction of Half-Ripe Fruit, and Water Fraction of Half-Ripe Fruit of Sesoot (Garcinia Picrorrhiza Miq.) with Liquid Chromatography-Mass Spectrometry (Lc-Ms) - Sri Utami; Erni H. Purwaningsih; Samuel J. Haryono; Chaidir Chaidir (Jurnal Health Sains, 2023)
Garcinia is a plant belonging to the family of Guttiferae or Cluciaceae and has more than 180 famous species. Most of Garcinia species contains many prenelated xanthones, biflavonoids, and benzophenones. Using Liquid Chromatography - Mass Spectrometry (LC-MS), the development of electrospray ionization (ESI) could be detected and could be applied to a wide range of molecular biology such as xanthones, biflavonoids, and benzophenones and their derivatives. This method with a high speed of scanning at once could be measured a high degree of multiplexing and many components can be measured with a single analysis. These results were separated and analyzed using literature software of Dictionary of Natural Product 2006. The ethanolic extract of ripe fruit (IC), the n-hexane fraction of half ripe (IIB), and the water fraction of half ripe fruit (IVB) of sesoot (G. picrorrhiza Miq.) showed that the major compounds of them were xanthones, benzophenones with their derivatives,  furanone and pyranone which were proven as cytotoxic to the brine shrimp nauplii using Brine Shrimp Lethality Test (BSLT) and to the doxorubicin-resistant breast cancer cell line of MCF-7, the doxorubicin-sensitive breast cancer cell line of T47D.